Broken Home as Inspiration in the Creative Process of Painting Art - Shafira, Tasya; Rajudin, Rajudin; Miswar, Miswar (V-art: Journal of Fine Art, 2023)
A broken home is defined as a family condition that is not harmonious and does not function like a peaceful and prosperous family, due to frequent disturbances and conflicts that lead to arguments and ultimately divorce. The "broken home" depicted in this artwork is inspired by childhood experiences. Its presence serves as a warning to prevent others from going through the same ordeal. This serves as the foundation for the creation of a two-dimensional painting. The approach employed in this creation is a representational form approach. The medium used is mixed media on canvas, utilizing the placard technique. The creative process involves preparation, design, embodiment, and presentation. This creative process has resulted in the creation of five pieces titled "Strict Parents," "Where is My Home," "Home-Sick," "5 Years Old," and "Traumatic."